Environmental Impact and Awareness of COVID-19 Pandemic on Solid Waste Management in Windhoek Municipality between 2019 and 2020, Namibia - Nwagbara, Victor Uzoma; Iyama , William Azuka (Research Advances in Environment, Geography and Earth Science Vol. 3, 2024)
This study was focused on the implications of COVID-19 pandemic on solid waste management in Windhoek, Namibia using Khomasdal, Katutura, Dorado Park, Otjomuse, Rocky Crest, Soweto and Hockland Park. There are records of several significant pandemics in human existence but the pandemic-related crises have caused enormous negative impacts on health, economies, and even national security globally. The cross-sectional survey design was employed while a simple random sampling model and well-structured questionnaire whose validity and reliability were tested and found suitable. The t-test analysis showed no significant relationship between waste generation and disposal practices (p < 0.05; t-start = 0.96). Tangible difference between the responses (p < 0.05 and t-start = 2.69) on the concept of awareness of COVID-19 pandemic but no significant difference between the responses on solid waste during the pandemic (p < 0.05; t-start = -0.31) and also for the influence of COVID-19 pandemic on solid waste management especially on the environment (p < 0.05; t-start = -1.792). Sixty (60%) of inhabitants complained of poor smell while 66% acknowledged the loss of jobs during the pandemic. Similarly, 64% of respondents agreed that the pandemic was not the cause of any disease outbreak. A very striking issue was the 82% who agreed to the fact that the contagious nature of the pandemic was due to sabotage. Waste management was not highly efficient (63%) as waste dumps were prevalently high within the period under review (60%). This study revealed that the COVID-19 pandemic really led to an increase in the volume of waste generated due to more food consumption, irregular disposal of waste, an increase in online shopping and a reduction in the number of waste management and workers for prevention of infection. There is an urgent need to further improve waste management practices during restrictions.